Probabilistic seismic fragility assessment of vertical storage tank with a floating roof. (February 2023) - Wang, Mengzhu; Sun, Zongguang; Sun, Jiangang; Cui, Lifu; Wu, Yujian
Abstract: Vertical storage tank is an important facility of oil depot, which may cause catastrophic accidents during strong earthquake, resulting in serious economic and environment consequences. The manuscript studies the seismic fragility of tank with a floating roof. A refined finite element model of the tank with three height-to-diameter ratios is developed. Time-history responses of sloshing wave height, base shear force and base bending moment of tank with and without a floating roof are analyzed. Then, time-history analysis of 55 ground motions is performed to establish seismic demand models for various responses and the most proper intensity measure is determined based on the dispersion and determination coefficient. Appropriate component-level and system-level damage states are defined by identifying possible failure modes during strong earthquake. Seismic fragility curves for different responses are derived for four damage states by cloud analysis. The results indicate that combined spectral acceleration is the most effective and sufficient IM and using only one component fragility to evaluate seismic performance may underestimate the tank system fragility. The results can provide practical advice for seismic risk assessment of individual tank or entire tank farm.